ANALISIS OPINI KONSUMEN TERHADAP JAMU GUJATI 59 DI PROVINSI BANTEN - Karyadi, Muhammad Rafael (Fakultas Dharma Duta, 2025)
Jamu is a hereditary heritage from our ancestors, jamu has also become part of our culture and natural wealth. Indonesia itself has natural wealth and herbal ingredients throughout Indonesia from sabang to merauke. That is what makes jamu brand companies have twisting the brain to carry out marketing strategies for their jamu brands, one of which is by increasing awareness of the brand itself which is associated with the strength of the impression stored in memory which is reflected in the ability of consumers to recall a brand under different conditions. So this study will analyze two variables that may affect consumer attitudes towards Gujati 59 itself, namely brand awareness and consumer attitudes towards the brand. The method chosen in the research is qualitative with a Focused Interviewed approach, because researchers will discuss public perceptions of the Gujati 59 Brand, in retrieving information from these data, in-depth interviews will be conducted to find out the public's perception of Gujati 59 itself. The conclusion obtained is that it can be concluded that the Gujati 59 herbal medicine brand has received a positive response from the community in the Banten area. Opinions that describe a positive evaluation of the product indicate that the jamu brand has succeeded in gaining trust and acceptance from consumers in the Banten region